Valuation of methodologies for mapping oligogenic trait loci in Recombinat Inbred Lines (RILs) doi: 10.4025/actasciagron.v36i1.17710 - Leonardo de Azevedo Peixoto; Adesio Ferreira; Marcia Flores da Silva Ferreira; Cosme Damião Cruz (Acta Scientiarum. Agronomy, 2014)
The present work aimed to compare the efficiencies of the Oligogenic Trait Mapping Method (OTMM) and Interval Method (IM) for detecting oligogenic trait loci (OTL) in Recombinant Inbred Line (RIL) populations of different sizes. Populations consisting of 200, 500 and 1,000 individuals were employed and 100 repetitions performed for each population size. Four characteristics were evaluated: C1, determined by two genes with 50 and 30% effects on expression of the characteristic; C2, governed by three genes with 50, 20 and 10% effects; C3, regulated by two genes, each with 40% effect; and C4, controlled by two genes, each with 50% effect. The IM was efficient at detecting OTL in all evaluated characteristics; however, for characteristics determined by two genes with effects between 40 and 50%, the OTMM was more efficient at detecting and localizing OTL in simulated marks. In contrast, the IM method was more efficient at detecting and localizing OTL in simulated marks when the gene effect ranged from 10 to 30%. As a result, because oligogenic characteristics are governed by genes with greater effects, the OTMM was considered the most efficient method to be used for this type of characteristic.